Gambaran Tingkat Kecemasan Pada Anak Usia 6-12 Tahun yang Mengalami Hospitalisasi di RSAU Dr. M. Salamun - Utami, Desi Sundari; Lugina, Dery Subhan (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The morbidity rate for children in Indonesia who are treated in hospitals is quite high, namely 15.26%, which is indicated by the number of children's rooms in both government and private hospitals. The National Center for Health Statistics estimates that 3 – 5 million children under the age of 15 are hospitalized each year. The most common problem experienced is anxiety disorders. Congestion is an event that easily occurs or spreads but is not easy to overcome because of non-specific causal factors. The amount of anxiety experienced by children when undergoing hospitalization has negative impacts that interfere with the child's development. Knowing the Description of Anxiety Levels in Children Aged 6-12 Years Who Experience Hospitalization. The research method used is descriptive research. The sampling technique used was Quota Sampling with a total of 90 respondents. The research instrument used was the Spence Children's Anxiety Scale (SCAS) questionnaire. The data analysis used was descriptive analysis (univariate), which aims to explain or describe the characteristics of each research variable. The research method used is descriptive research. The sampling technique used was Quota Sampling with a total of 90 respondents. The research instrument used was the Spence Children's Anxiety Scale (SCAS) questionnaire. The data analysis used was descriptive analysis (univariate), which aims to explain or describe the characteristics of each research variable.Conclusion: The conclusion is that children aged 6-12 years as a result of hospitalized at RSAU dr. M. Salamun experienced moderate levels of anxiety as many as 47 respondents (52.2%). Keywords: Anxiety Level, Children Aged 6-12 Years, Hospitalization  ABSTRAK Angka kesakitan anak di Indonesia yang dirawat di rumah sakit cukup tinggi yaitu 15,26% yang ditunjukkan dengan selalu penuhnya ruangan anak baik rumah sakit pemerintah maupun swasta.  The National Centre for Health Statistic memperkirakan bahwa 3 – 5 juta anak di bawah usia 15 tahun menjalani hospitalisasi setiap tahun. Masalah yang paling banyak di alami adalah gangguan kecemasan. Kecemasan merupakan kejadian yang mudah terjadi atau menyebar namun tidak mudah diatasi karena faktor penyebabnya yang tidak spesifik. Banyaknya kecemasan yang dialami anak ketika menjalani hospitalisasi menimbulkan dampak negatif yang mengganggu perkembangan anak. Mengetahui Gambaran Tingkat Kecemasan Pada Anak Usia 6-12 Tahun Yang Mengalami Hospitalisasi. Metode penelitian yang digunakan adalah penelitian deskriptif. Teknik sampling yang digunakan adalah Quota Sampling dengan jumlah 90 responden. Instrumen penelitian yang  digunakan adalah Quesioner Spence Children’s Anxiety Scale (SCAS), Analisis data yang digunakan adalah analisa deskriptif (univariat), yang bertujuan untuk menjelaskan atau mendeskripsikan karakteristik setiap variabel penelitian. Hasil penelitian  anak yang mengalami hospitalisasi Di RSAU dr. M. Salamun yaitu 47 Responden (52,2%)  kategori kecemasan sedang, 32 Responden (35,6%) kategori kecemasan ringan dan 11 responden (12,2%) kategori kecemasan berat.  Kesimpulkan bahwa anak usia 6-12 tahun yang mengalami hospitalisasi Di RSAU dr. M. Salamun mengalami tingkat kecemasan sedang sebanyak 47 Responden (52,2%). Kata Kunci: Tingkat Kecemasan, Anak Usia 6-12 Tahun, Hospitalisasi